COVID-19 causing rhabdomyolysis requiring hemodialysis in a young adult. Issue 4 (9th June 2022) - Mittal, Nitish; Del Rio-Pertuz, Gaspar; Abohelwa, Mostafa
Abstract: Cases of rhabdomyolysis causing myoglobinuria in post–COVID-19 patients have been seen, and exact mechanisms behind it seem multifactorial. Some patients have severe myoglobinuria with highly elevated creatinine phosphokinase levels requiring urgent hemodialysis to keep creatinine and blood urea nitrogen levels under control and protect the kidneys from long-term damage. Here, we present a case of a 34-year-old man with a history notable for autism and hypertension who was admitted to the hospital for COVID-19 viral pneumonia and discharged without major complications. After 3 weeks, he came to the emergency room with decreased mental status and asterixis. He had red-colored urine and acute kidney injury secondary to rhabdomyolysis. His creatinine phosphokinase was 289, 500 mcg/L—a level never reported before. The patient did not respond to aggressive intravenous fluids, so he was started on hemodialysis. After 1 week, he showed clinical improvement, and he was taken off dialysis in 2 weeks.